Rational design of 3D hollow cube architecture for next-generation efficient aqueous asymmetric supercapacitors. (May 2023) - Chavan, G.T.; Amate, Rutuja U.; Lee, Hajin; Syed, Asad; Bahkali, Ali H.; Elgorban, Abdallah M.; Jeon, Chan-Wook
Abstract: Tri-metallic sulfides (TMS) with hollow/porous architectures have attracted considerable attention for the fabrication of efficient hybrid supercapacitors. Thus, for the first time, we report the rational design of tailored 3D hollow cube architecture for asymmetric supercapacitor (ASC) device applications. The MnCoNiS/Ni foam (NF) electrodes grown at a hydrothermal deposition time of 15 h with 3D hollow cube morphology (labelled as MCNS-4) delivers excellent specific capacitance (Cs ) of 2831.85 F g −1 and areal capacitance (CA ) of 14.2 F cm −2 at 10 mA cm −2 . The MCNS/NF//AC/NF-based ASC device exhibited a high Cs of 177.65 F g −1, CA of 534 mF cm −2, a power density of 1416.71 W kg −1 (4.25 mW cm −2 ), and an energy density of 71.30 Wh kg −1 (0.214 mWh cm −2 ) at 1.7 V potential. The ASC device delivers high rate capability and exceptional cyclic stability of 78 % after 10, 000 cycles with 94 % coulombic efficiency. Thus, the outstanding charge storage performance and redox activity of ASC can be credited to the synergistic effects of the Ostwald ripening process, heat treatment, fine-tuning of morphology, and low charge transfer resistance. Finally, the commercial blue LED was illuminated for >4 min by connecting two ASC devices in series. Hence, encouraging device performance demonstrates that MnCoNiS electrodes are a highly competent contender for the progress of next-generation, and practical energy storage devices to reduce power hunger. Graphical abstract: Unlabelled Image Highlights: For the first time a tailored 3D hollow cube architecture was developed. The MCNS-4 electrode realized high specific capacitance of 2831.85 F g −1 at 10 mA cm −2 . Hierarchical 3D hollow cube morphology enables rapid ion transport. The charge-storage kinetics was thoroughly studied by using CV data. The ASC delivers PD of 1416.71 W kg −1 and ED of 71.30 Wh kg −1 with excellent stability.